The 'Red Radio Ring': ionized and molecular gas in a starburst/active galactic nucleus at z ∼ 2.55. Issue 2 (3rd July 2019) - Harrington, Kevin C; Vishwas, A; Weiß, A; Magnelli, B; Grassitelli, L; Zajaček, M; Jiménez-Andrade, E F; Leung, T K D; Bertoldi, F; Romano-Díaz, E; Frayer, D T; Kamieneski, P; et al.
ABSTRACT: We report the detection of the far-infrared (FIR) fine-structure line of singly ionized nitrogen, [N ii ] 205 μ m , within the peak epoch of galaxy assembly, from a strongly lensed galaxy, hereafter 'The Red Radio Ring'; the RRR, at z = 2.55. We combine new observations of the ground-state and mid-J transitions of CO ( J up = 1, 5, 8), and the FIR spectral energy distribution (SED), to explore the multiphase interstellar medium (ISM) properties of the RRR . All line profiles suggest that the H ii regions, traced by [N ii ] 205 μ m , and the (diffuse and dense) molecular gas, traced by CO, are cospatial when averaged over kpc-sized regions. Using its mid-IR-to-millimetre (mm) SED, we derive a non-negligible dust attenuation of the [N ii ] 205 μ m line emission. Assuming a uniform dust screen approximation results a mean molecular gas column density >10 24 cm −2, with a molecular gas-to-dust mass ratio of 100. It is clear that dust attenuation corrections should be accounted for when studying FIR fine-structure lines in such systems. The attenuation corrected ratio of L_N II205 / L_IR(8\!-\!1000 μ m) = 2.7 × 10^-4 is consistent with the dispersion of local and z > 4 SFGs. We find that the lower limit, [N ii ] 205 μ m -based star formation rate (SFR) is less than the IR-derived SFR by a factor of 4. Finally, the dust SED, CO line SED, and L_N II205 line-to-IR luminosity ratio of the RRR is consistent with a starburst-powered ISM.